Clinico-Genomic Profiling of Conventional and Dedifferentiated Chondrosarcomas Reveals TP53 Mutation to Be Associated with Worse Outcomes - Denu, Ryan A.; Yang, Richard K.; Lazar, Alexander J.; Patel, Shalin S.; Lewis, Valerae O.; Roszik, Jason; Livingston, J. Andrew; Wang, Wei-Lien; Shaw, Kenna R.; Ratan, Ravin; Zarzour, Maria A.; Bird, Justin; et al. (Clinical cancer research, 2023)
Chondrosarcomas are the most common primary bone tumor in adults. Isocitrate dehydrogenase 1 (IDH1) and IDH2 mutations are prevalent. We aimed to assess the clinico-genomic properties of IDH mutant versus IDH wild-type (WT) chondrosarcomas as well as alterations in other genes. We included 93 patients with conventional and dedifferentiated chondrosarcoma for which there were available clinical next-generation sequencing data. Clinical and genomic data were extracted and compared between IDH mutant and IDH WT chondrosarcomas and between TP53 mutant and TP53 WT chondrosarcomas. IDH1 and IDH2 mutations are prevalent in chondrosarcoma (50.5%), more common in chondrosarcomas arising in the extremities, associated with higher age at diagnosis, and more common in dedifferentiated chondrosarcomas compared with grades 1-3 conventional chondrosarcoma. There was no difference in survival based on IDH mutation in univariate and multivariate analyses. TP53 mutation was the next most prevalent (41.9%) and is associated with worse overall survival and metastasis-free survival in both univariate and multivariate analyses. TP53 mutation was also associated with higher risk of recurrence following curative-intent surgery and worse survival among patients that presented with de novo metastatic disease. IDH mutations are prevalent in chondrosarcoma though were not associated with survival outcomes in this cohort. TP53 mutations were the next most common alteration and were associated with worse outcomes.